Anxiety and Sun Exposure as Triggers for Herpes Labialis: A Case Report and Review of Literature - Putri NT; Octaviani DK; Zakiawati D (International Medical Case Reports Journal)
Nadia Tiara Putri,1,* Dhini Karina Octaviani,1,* Dewi Zakiawati2,* 1Oral Medicine Specialist Program, Faculty of Dentistry Universitas Padjadjaran, Bandung, Indonesia; 2Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Nadia Tiara Putri, Oral Medicine Specialist Program, Faculty of Dentistry Universitas Padjadjaran, Sekeloa Selatan Street No. 1, Bandung, 40132, Indonesia, Tel +62 81296818202, Fax +62 22 7794121, Email nadia21016@mail.unpad.ac.idIntroduction: Herpes labialis (HL) is a prevalent viral infection caused by herpes simplex virus type 1 (HSV-1), affecting a significant portion of the global population. The reactivation of HSV-1 leading to HL can be triggered by various factors, including psychosocial factors (depression, stress, and anxiety), exposure to ultraviolet light, a febrile environment, and specific dietary inadequacy.Purpose: This case report explores the association between HL, psychological conditions, and sun exposure.Case Report: A 20-year-old male patient came with a chief complaint of swollen lips with tiny pimples for two days, accompanied by malaise. The patient was working as a florist in a sun-exposed area and experiencing stress due to financial difficulties. Extraorally, multiple vesicles were found on the left side of the upper lip, surrounded by erythema, and painless. Laboratory examinations showed a reactive HSV-1 IgG. The depression, anxiety, and stress scale-21 (DASS-21) questionnaire showed an extremely severe level of anxiety.Case Management: The patient was given systemic and topical acyclovir, multivitamins, hyaluronic acid mouthwash, and petroleum jelly. In addition, the patient was advised to reduce the frequency of sun exposure, apply sunscreen, and seek professional help to manage the anxiety. A review of eight case reports related to HL from 1994– 2024 has been reported in this literature and emphasizes the connection of HL with psychological factors and sun exposure.Conclusion: This case underscores the potential link between anxiety, sun exposure, and the onset of HL. Understanding these associations is crucial for effective management and prevention strategies.Keywords: anxiety, DASS-21, herpes labialis, HSV-1, oral diseases, sun exposure